Revitalizing the First-Suburbs: The Importance of the Social Capital-Community Development Link in Suburban Neighborhood Revitalization -A Case Study - JoAnna Mitchell-Brown (The University of Alabama, 2022)
This article examines the link between social capital and community development. The purpose is to increase the understanding of social capital and its role and function in the neighborhood revitalization process within first-suburbs (also known as inner-ring suburbs). In doing so, it briefly outlines the challenges of the first-suburbs, in light of suburban decline. It also addresses the role and function of social capital as a community development tool within the first-suburbs. Finally, this piece provides case study examples describing the context in which first-suburban communities mobilize and use their social capital to implement community development initiatives, with the focus on the Greater Cincinnati region.